Analysis of Emotional Intelligence of Scheduled Caste Students In Relation to Home Environment at Secondary Level: Exploring the origins and impact of emotional intelligence in the schooling of scheduled caste students (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Inthe early part of 20th century psychologists used intelligence to explain individualdifferences in order to facilitate schooling. Since then, the issue of thenature of intelligence has not been settled. Even today we do not have anycommonly agreed upon definition. Emotional Intelligence (EI) is one of therecent developments in the area of intelligence. Though Emotional Intelligencegained popularity towards the end of the twentieth century, its origin can betraced to early philosophical discourses.